The two Koreas in 2000: Sustaining recovery and seeking reconciliation - Köllner, Patrick; Beck, Peter M.; Noland, Marcus; Wein, Roland; Ahn, Se-young; Croissant, Aurel; Jeon, Bang-nam; Steinberg, David; Merrill, John; Winder, Joseph A. B. (2000)
Part 1: Assessing South Korea's economic reforms. Köllner, Patrick: Coping with legacy of unbalanced development. - S. 1-15. Beck, Peter M.: Korea's embattled chaebol.- S. 16-28. Jeon Bang-nam ; Ahn Se-young: Korean attitudes toward foreign firms. - S. 29-41. Noland, Marcus: From patron to partner: U.S.-South Korea trade relations. - S.42-52. Part II: The 2000 National Assembly elections and beyond. Steinberg, David: Korean politics: the new and the old. - S. 53-61. Wein, Roland: Civic organizations under the "government of the people". - S. 62-76. Croissant, Aurel: Calibrating democracy for a unified Korea. - S. 77-93. Part III: North-South relations: a new era of reconciliation? Winder, Joseph A. B.: The economic dynamics of the Korean peninsula peace process. - S. 95-109. Merrill, John: A perspective on the sunshine policy. - S. 110-114